2020
DOI: 10.1002/ijgo.13454
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and preferences for self‐collected screening for cervical cancer within health systems in rural Uganda: A mixed‐methods approach

Abstract: Objective To understand the knowledge, preferences, and barriers for self‐collected cervical cancer screening (SC‐CCS) and follow‐up care at the individual and health system level to inform the implementation of community‐based SC‐CCS. Methods Surveys and focus group discussions (FGDs) with women and FGDs with healthcare providers were conducted in Uganda. Survey data were analyzed using frequencies and FGD data were analyzed using thematic content analysis. Data were triangulated between methods. Results Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Twenty-two articles were excluded at the full article screening stage 17–38. Of the 22 excluded, 14 were conducted on participants less than 25 years old,17 21–23 25–27 29 30 32–34 36 37 7 studies18–20 24 28 31 38 did not measure acceptability, characteristics of acceptability or sampling preference and 1 study was conducted outside SSA 35. The 19 remaining studies39–57 were incorporated into the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two articles were excluded at the full article screening stage 17–38. Of the 22 excluded, 14 were conducted on participants less than 25 years old,17 21–23 25–27 29 30 32–34 36 37 7 studies18–20 24 28 31 38 did not measure acceptability, characteristics of acceptability or sampling preference and 1 study was conducted outside SSA 35. The 19 remaining studies39–57 were incorporated into the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Self-sampling methods could substitute gynecological examinations in places with a lack of health infrastructure, being cost-effective and well-accepted options, in order to increase cancer screening uptake [ 26 , 35 ]. Moreover, since the lockdown due to COVID-19 has decreased cervical cancer screening, self-sampling methods could be part of the solution for similar situations [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies on the use of HPV-based screening in LMICs have demonstrated that HPV testing on self-collected specimens is comparable to provider-collected specimens for detection of cervical precancer/cancer, 4,5 is cost-effective, 6,7 and highly acceptable across many countries. [8][9][10][11]12 Use of HPV testing for primary screening in LMICs is limited, however, with less than 5 African countries recommending HPV testing as a primary screening method. 13 This limited use is partly due to the cost and logistical challenges of incorporating HPV testing within existing "screen & treat" programs in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies on the use of HPV-based screening in LMICs have demonstrated that HPV testing on self-collected specimens is comparable to provider-collected specimens for detection of cervical precancer/cancer, 4,5 is cost-effective, 6,7 and highly acceptable across many countries. 811,12…”
Section: Introductionmentioning
confidence: 99%